Ritually breaking Lapita pots: or, can we get into the minds of Oceanic first settlers? A discussion. Issue 1 (22nd April 2013) - Sand, Christophe; Marshall, Yvonne; Sheppard, Peter; Spriggs, Matthew; Chiu, Scarlett; Sand, Christophe
Abstract One of the striking characteristics of Lapita archaeology during the past century has been the very limited number of preserved whole or nearly whole pots found in excavations. This appears odd for ceramics mostly interpreted in the scientific literature as non‐utilitarian and carrying social or ritual symbolism. The clear connection between dentate‐stamped pots and complex burial rituals at the Teouma site (Vanuatu), along with studies on pottery breakage carried out in other parts of the world, allows the canvassing of a theoretical model that explains the apparent absence of logic in finding numerous Lapita pots reduced to small potsherds. By positioning the analysis in a framework relying on the specific behaviour of Pacific Islanders regarding the "invisible" and by using ethnographic Melanesian rituals as examples of how "natural forces" can be controlled, this paper proposes a hypothetical reconstruction of one of the possible ceremonies that may have been practiced by Oceanic explorers in newly settled islands.